Eksplorasi Bentuk dan Teknik Penciptaan Keramik Melalui Metode Cetak - I Komang Surya Adi Putra; Rai Sunarini, Ni Made; Berata, I Made (Hastagina : Jurnal Kriya Seni, 2025)
This creation aims to explore various figurative forms in ceramic art while developing an efficient forming technique with high aesthetic value through the application of the slip casting method. The main issues addressed include how to create ceramic works with strong visual character using slip casting techniques and how to design a consistent and effective production process. The creation process applies Sp. Gustami’s method, which consists of three stages: exploration, design, and realization. The exploration stage is used to generate ideas and form concepts, which are then manifested in design plans, model (master) making, and mold production using plaster. The realization process is carried out through the slip casting technique, followed by general ceramic production stages such as drying, firing, and finishing. The exploration of forms focuses on animal-themed works, resulting in ceramic pieces shaped like iguanas, horses, and turtles. The application of the slip casting technique in this creation has proven capable of reproducing forms consistently according to the original model, without reducing creative freedom or aesthetic value. Furthermore, the slip casting method demonstrates greater efficiency compared to manual forming techniques. It allows the creation of ceramics with complex structures and finely detailed surfaces, including curves, protrusions, textures, and small ornaments that enhance the visual character of the works. The results of this creation are expected to serve as a reference for artisans and creative industry practitioners in developing ceramic products based on casting techniques, both for artistic purposes and large-scale production.